Micro-scale horizontal-axis wind turbines get new air foil - REDDY, P.NAVEEN; REDDY, POLAMURI RAMA MOHAN (The journal of contemporary issues in business and government, 2019)
The purpose of this research was to find the optimum dimensions for the blades of tiny, horizontal-axis wind turbines operating at low wind speeds. The blades were designed with efficiency in mind using the blade element momentum (BEM) theory of blade optimization. Single (W1 & W2) and multistage (W3) rotors with radii of 0.2 m, 0.4 m, and 0.6 m, and a variety of blade geometries, were studied. The BEM theory was implemented using MATLAB and XFoil to design a series of six innovative air foils (NAF-Series) for low Reynolds number applications on tiny horizontal axis wind turbines. In order to create the experimental blades, a 3D printer was used to create a virtual model of the blade. XFoil software was used to study the performance of recently developed air foils at Reynolds numbers of 100,000, including the NAF3929, NAF4420, NAF4423, NAF4923, NAF4924, and NAF5024. Tip speed ratios between 3 and 10 and angles of attack between 2 and 20 were examined. The power coefficient, lift coefficient, drag coefficient, and lift-to-drag ratio were optimized and studied by varying these parameters in MATLAB and XFoil software. Both the single- and multi- stage rotors had a cut-in wind velocity of around 3 meters per second. The optimum values for the ratio of tip speed to axial displacement were 0.08m, and the angle of attack was 6 degrees. At low Reynolds numbers, the proposed NAF-Series air foil blades outperformed the basic SG6043 and NACA4415 air foil designs in terms of aerodynamic performance and maximum output power.